2000
DOI: 10.1111/j.1469-7793.2000.t01-1-00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in adult cat visual cortex (area 17) following circumscribed monocular lesions of all retinal layers

Abstract: It has been shown in a number of previous studies that in adult cats discrete retinal lesions induce a reorganization of visuotopic maps in that part of striate cortex (area 17; V1) in which the lesioned part of the retina was represented (Kaas et al. 1990;Chino et al. 1992Chino et al. , 1995Gilbert & Wiesel, 1992;Darian-Smith & Gilbert, 1995;Schmid et al. 1995Schmid et al. , 1996Calford et al. 1999). Projected onto area 17, these lesions represented an area (lesion projection zone; LPZ) typically 3 to 5 mm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 49 publications
(117 reference statements)
9
97
1
Order By: Relevance
“…This finding corroborates the numerous animal studies suggesting that V1 retains a remarkable degree of plasticity even in adulthood (Kaas et al, 1990;Heinen and Skavenski, 1991;Gilbert and Wiesel, 1992;Chino et al, 1992;Darian-Smith and Gilbert, 1995;Schmid et al, 1996;Calford et al, 2000), and contradicts previous reports of no cortical reorganization in the adult animal visual system (Horton and Hocking, 1998;Smirnakis et al, 2005a). Additionally, our results support the finding of large-scale reorganization after deafferentation of human adult visual cortex in patients with macular degeneration (Baker et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This finding corroborates the numerous animal studies suggesting that V1 retains a remarkable degree of plasticity even in adulthood (Kaas et al, 1990;Heinen and Skavenski, 1991;Gilbert and Wiesel, 1992;Chino et al, 1992;Darian-Smith and Gilbert, 1995;Schmid et al, 1996;Calford et al, 2000), and contradicts previous reports of no cortical reorganization in the adult animal visual system (Horton and Hocking, 1998;Smirnakis et al, 2005a). Additionally, our results support the finding of large-scale reorganization after deafferentation of human adult visual cortex in patients with macular degeneration (Baker et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…Initial neural evidence came from adult animal studies in which a region of the primary visual cortex (V1) was deafferented by means of retinal lesions (Kaas et al, 1990;Heinen and Skavenski, 1991;Gilbert and Wiesel, 1992;Chino et al, 1992;Darian-Smith and Gilbert, 1995;Schmid et al, 1996;Calford et al, 2000). Like deafferented neurons in the S1, deafferented V1 neurons began responding to stimuli that normally activated the adjacent V1 cortex.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, both cat and monkey studies provide evidence for retinotopic reorganization as a result of retinal deafferentation (Kaas et al, 1990;Heinen & Skavenski, 1991;Gilbert & Wiesel, 1992;Chino et al, 1992Chino et al, , 1995Darian-Smith & Gilbert, 1994, 1995Calford et al, 2000). Extensive reviews on cortical plasticity of sensory and motor organization can be found in Chino (1995), Gilbert (1998), and Kaas and Collins (2003).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Cat and monkey studies have shown that reorganization in adult mammalian visual cortex occurs following visual field loss (Kaas et al, 1990;Heinen & Skavenski, 1991;Gilbert & Wiesel, 1992;Chino et al, 1992Chino et al, , 1995Darian-Smith & Gilbert, 1994, 1995Calford et al, 2000). Prior to these studies, prevailing wisdom held that connections along the retinocortical visual pathways are very rigid following a developmental critical period (weeks old) (see Boothe et al, 1985 for a review).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Firstly, partial optic nerve damage or cortical tissue loss may lead to a reduced physiological signaling power and to a loss of firing synchrony of neuronal assemblies, thus increasing processing time. Secondly, there is an extensive remapping and reorganization of the visual field representation after pre-and post-chiasmatic damage as shown in animal model studies [34][35][36][37], as well as behavioral [38] and fMRI studies in patients [31][32][33]39]. Such receptive field reorganization is believed to be mediated by mechanisms involving plasticity of intrinsic cortical horizontal connections [40].…”
Section: Perceptual Deficits In the ''Intact'' Visual Field Of Patientsmentioning
confidence: 99%